2008
DOI: 10.1111/j.1365-2400.2008.00623.x
|View full text |Cite
|
Sign up to set email alerts
|

The level of predation used as an indicator of tagging/handling effects

Abstract: In most telemetry studies, there can be adverse effects of capture, handling and tagging. Possible tagging effects include impaired competitive performance and predator avoidance. These effects are not easily studied in the laboratory, and field studies include too much variability to test such indirect effects. Predation experiments were conducted in four outdoor ponds to test for the possible effects of transport/handling and tagging by surgical implanting. Pikeperch, Sander lucioperca (L.), were used as pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 23 publications
3
21
0
Order By: Relevance
“…However, differences were not observed in predation between smolts tagged with dummy radio transmitters and untagged ones in experimental conditions (Jepsen et al . ), lending support to similar, earlier results for radio‐tagged and untagged smolts in a study conducted in a Danish reservoir (Jepsen et al . ).…”
Section: Discussionsupporting
confidence: 89%
“…However, differences were not observed in predation between smolts tagged with dummy radio transmitters and untagged ones in experimental conditions (Jepsen et al . ), lending support to similar, earlier results for radio‐tagged and untagged smolts in a study conducted in a Danish reservoir (Jepsen et al . ).…”
Section: Discussionsupporting
confidence: 89%
“…Other mortality factors could include tagging effects, but these transmitters were not expected to cause high mortality as studies have shown no or little negative effects of similar surgical implants (Jepsen et al. 2006, 2008a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this proportion takes into account the number of PIT tags regurgitated outside the colony as well as undetected tags in the colony (see also Frechette et al., ). The overall question of whether capture, handling and tagging of smolts increase the probability of being eaten by a cormorant is relevant, but hard to resolve (see Jepsen, Christoffersen & Munksgaard, ). However, since a range of different methods provided similar predation estimates suggests that this was not a major problem in these studies.…”
Section: List Of Studies Summarising Estimates Of Predation By Cormormentioning
confidence: 99%